The community resilience of tourism agents in times of the COVID-19 pandemic.: Un análisis desde el territorio - Álvarez Meneses, Tannia; Universidad Pedagógica y Tecnológica de Colombia; Gamba Niño, Jorge Enrique; Universidad Pedagógica y Tecnológica de Colombia; Botía Flechas, Clara Judyth; Universidad Pedagógica y Tecnológica de Colombia (UPTC Editorial, 2023)
In the context of the pandemic and the undeniable economic crisis that has left global tourism activity, a latent phenomenon is present in local communities in the face of adversities caused, whether by natural disasters, social conflicts or in this particular case by public health reasons in tourist destinations, and it is the concept of community resilience, which has made it possible to analyze the different resources, means and strategies that collectives, families or cultural groups use to face and overcome sociopolitical or ecological threats. This perspective recognizes that resilience at the collective level is achieved thanks to  interrelationships and interactions of community characteristics that integrate shared and organized reconstruction actions, and more than individual activities, the social entity is addressed as such. the research that gives rise to this manuscript is based on the concept of community resilience and focuses on establishing the resilience capacity of local communities in times of pandemic for the reactivation of tourism in the department of Boyacá and in Colombia.